The philosopher of Palo Alto Mark Weiser, Xerox PARC, and the original Internet of things - Tinnell, John (The University of Chicago Press, 2023)
"As a pioneer of ubiquitous computing-the embedding of technology in everyday objects from thermostats to doorbells-computer scientist Mark Weiser's descriptions of smart homes, now thirty years later, might seem to approach our reality. Weiser's views certainly influenced our technology's developers-his 1991 Scientific American article "The Computer for the 21st Century" was flagged a must-read by Microsoft's Bill Gates and then circulated among the day's digirati, including those Silicon Valley insiders who crowded his beer garden-based "office hours". Unlike many of his contemporaries, Weiser's vision was motivated by the philosophies of Michael Polanyi and Martin Heidegger, collaboration with anthropologists such as Lucy Suchman, and insights from artists including Natalie Jeremijenko. He hoped to realize "tacit computing" as an escape from a single attention-grabbing screen as a portal to work, entertainment, and education. When rivals such as Nicholas Negroponte at MIT's Media Lab championed the development of smart agents (the ancestors of Siri and Alexa) or pervasive sensing in wearable technologies (proto-Fitbits or Apple Watches), Weiser balked. Weiser wanted computers to be something closer to the white cane a person with low vision might use to navigate the world. Good technology, he argued, should not mine our experiences for data to sell or demand our attention. Technology should not rob its users of the hardships that establish their expertise, but instead give them the ability to conceive of the world in new ways. In this compelling biography of a person and idea, digital studies scholar John Tinnell shows Weiser, who died of cancer at 46, would be heartbroken if he had lived to see the ways we use technology today. Informed by deep archival research and interviews with Weiser's family and Xerox PARC colleagues, this book uses Weiser's life to offer a new history of today's technological reality, an inside view of Xerox PARC during its heyday, and a compelling vision of what computers failed to be"-- Provided by publisher.